DYNAMIC CAPABILITY, ENVIRONMENTAL MANAGEMENT PRACTICES, AND GOVERNMENT SUPPORT AS FACTORS INFLUENCING GREEN ENTREPRENEURSHIP SUCCESS IN MALAYSIAN TOURISM SECTOR - Zaidey, Nur Syahirunnisaa’ Raden Azlane; Saad, Mohd Najib (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
The importance of green entrepreneurship as a method of enhancing sustainable development within the Malaysian tourism sector has continued to increase. However, even though numerous national sustainability efforts have been executed, the medium-sized tourism enterprises continue experiencing structural, business, and ability-associated issues that hinder the realization of green entrepreneurial triumphs. To address this gap, the present study considers the success of green entrepreneurship through the consideration of medium-sized enterprises in the Malaysian tourism sector. The data will be collected by use of a cross-sectional research design, where the researcher will concentrate on 373 companies by administering an online survey. This research study will take place with SPSS version 30.0 to perform descriptive analysis and version 4.0 of Partial Least Squares Structural Equation Modelling (PLS-SEM) version 4.0 to examine the correlation between the constructs. This study aims to discover the key antecedents of the success of green entrepreneurship empirically and explain how they are related to each other to generate evidence-based results that can enhance the process of policymaking, strategic decision-making at the enterprise level, and overall transition of Malaysia to a more resilient and sustainable tourism ecosystem.